“逆风如解意，容易莫摧残” ：论电视剧《后宫甄嬛传》中清宫女子的生存之道 = If wind sees their strong will, let such ordeal ceases : the survival of imperial concubines in The Legend of Zhen Huan - 曹瑜飞 Chau, Yee Fei (2014)
本文将解读郑晓龙导演所改编的清代宫廷剧《后宫甄嬛传》。此剧透过一群在清代后宫中生活的女性，再现了以甄嬛为中心，尔虞我诈的宫廷斗争。电视剧改编自架空网络小说，剧情由历史与现实紧密结合，虚实交错，使观众在观看的过程中产生由虚拟到现实的潜意识场景。此外，本文主要通过女性视角剖析主角——甄嬛和与其周旋的女子，从剧情中看女性如何塑造自身在封建王朝的身份地位与社会认同，贯彻自己的生存之道。《后宫甄嬛传》实为现代社会的缩影，观看的过程就是“自我”表象化的途径，引起共鸣的同时也让观众获得一把窥探内心的明镜，并重新反思现代女性的生存模式进而领悟“时代在变，人性不变”的真理。This article will interpret “The Legend of Zhen Huan”,a court drama set during Qing Dynasty period and adapted by Director Zheng Xiao Long.The drama tells a story of Zhen Huan and a group of women living in the harem. It depicts the struggles and intrigues in the palace. Originally a novel, this story overlapping of reality with fantasies in the plot combined with a mixture of reality and historical knowledge, has given the audience a platform to imagine the scene subconsciously. In addition, this thesis analyzes the main protagonist from a feminist perspective. As seen from the story, Zhen Huan and the other women have shown the identity and social status of the women in a dynasty that was conservative. It helps us to reconsider the survival circumstance of contemporary women."The Legend of Zhen Huan" is an exact miniature of a modern society. Watching the drama allows the audience to understand themselves and realized the truth that “Time does change, but human nature does not. ”